Production of Specialized Transformation Vectors for the Production of Biodegradable Plastics in Transgenic Arabidopsis and Oil Palm - Mat Yunus, Abdul Masani (2006)
Polyhydroxyalkanoates (PHAs), such as polyhydroxybutyrate (PHB) and polyhydroxybutyrate-co-hydroxyvalerate (PHBV) are bacterial polyesters, which can be used to produce biodegradable products. Since the mass production of PHAs in bacteria via fermentation is expensive, the production of PHAs in plants may be an attractive alternative. The production of PHB in plants required genetic engineering of phbA, phbB and phbC genes of Ralstonia eutropha, whereas, the bktB, phbB, phbC genes of R. eutropha and tdcB gene of Escherichia coli were required for PHBV production. In this study, each of these gene was fused with the transit peptide (Tp) of oil palm acyl-carrier-protein (ACP), and driven by the oil palm leaf-specific promoter (LSP1), for targeting into the plastids of leaf cells. In total, four transformation vectors, pLSP15 (PHB) and pLSP20 (PHBV), pLSP13 (PHB) and pLSP23 (PHBV) were constructed for the transformation of Arabidopsis and oil palm, respectively. Each vector contained the phosphinothricin acetyltransferase gene (Bar) driven by CaMV35S promoter in pLSP15 and pLSP20, and ubiquitin promoter in pLSP13 and pLSP23, as plant selectable marker. Matrix attachment region of tobacco (RB7MAR) was also included, to stabilize the transgene expression and to minimize gene silencing due to positional effects. Restriction enzymes, polymerase chain reaction (PCR) and DNA sequencing were used to verify all the constructed vectors. Arabidopsis transformation produced T1 transgenic Arabidopsis plants with normal phenotypes at a transformation efficiency of 0.2%~1.0%. PCR and Southern analyses were used to confirm the insertion of the transgenes. Nile blue A staining of these T1 plants demonstrated the accumulation of PHB granules in the leaf. The initial screening of Basta-resistant oil palm embryogenic calli transformed with pLSP13 using PCR demonstrated the presence of Bar and PHB genes in transformed oil palm.